Pengaruh Gaya Kepemimpinan dan Budaya Organisasi Terhadap Kinerja Pegawai PT Bank BTN (PERSERO) Kantor Cabang Kuningan Jakarta Selatan - Riri Oktarini; Juwita Ramadani Fitria; Ana Septia Rahman (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
The purpose of this research is to determine the influence of leadership style and organizational culture on employee performance to improve employee performance at PT Bank BTN (Persero) Kuningan Branch Office, South Jakarta, partially and simultaneously. The method used is a quantitative method with a causal associative approach. The population in this study were employees of PT Bank BTN (Persero) Kuningan Branch Office, South Jakarta, with a sample of 50 respondents, data collection techniques using interviews and questionnaires. Data analysis uses validity tests, reliability tests, classical assumption tests, linear regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing using SPSS version 25. The results of this research are that the influence of leadership style partially has a positive and significant effect on Employee Performance with regression equation Y = 14.689+0.667 (X1), the correlation coefficient is 0.765, meaning that the two variables have a low relationship with a coefficient of determination of 0.584 and the hypothesis test obtained tcount > ttable or (3.270 > 2.011) so H01 is rejected and Ha1 is accepted. Organizational culture partially has a positive and significant effect on employee performance with the regression equation Y = 12.187+1.299 (X2) with a correlation coefficient of 0.755, meaning that the two variables have a low relationship with a coefficient of determination of 0.570 and the hypothesis test obtained is tcount > ttable or (3.675 > 2.011) then H02 is rejected and Ha2 is accepted. The influence of leadership style and organizational culture simultaneously has a positive and significant effect on employee performance with the multiple linear regression equation Y = 10.889 + 0.387 (X1) + 0.633 (X2). The correlation coefficient value obtained was 0.755, meaning that the independent variable and the dependent variable had a moderate relationship with a coefficient of determination of 63.2% while the remaining 36.8% was influenced by other factors not examined in this research. Hypothesis testing obtained a value of Fcount> Ftable or (40.443 > 3.20), thus Ho3 was rejected and Ha3 was accepted.